2023
DOI: 10.1088/1758-5090/acb6b7
|View full text |Cite
|
Sign up to set email alerts
|

Fish scale containing alginate dialdehyde-gelatin bioink for bone tissue engineering

Abstract: The development of biomaterial inks suitable for biofabrication and mimicking the physicochemical properties of the extracellular matrix is essential for bioprinting technology in tissue engineering applications. The use of animal-derived proteinous materials, such as jellyfish collagen, or fish scale gelatin, has become an important pillar in biomaterial ink design to increase the bioactivity of hydrogels. However, besides the extraction of proteinous structures, the use of structurally intact fish scales as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In addition, a composite biomaterial ink composed of Fish Scale and alginate dialdehyde (ADA)-Gel for the fabrication of 3D cell-laden hydrogels using mouse pre-osteoblast MC3T3-E1 cells was revealed as a suitable biomaterial ink formulation with great potential for 3D bioprinting for bone TE applications [62].…”
Section: Gelatinmentioning
confidence: 99%
“…In addition, a composite biomaterial ink composed of Fish Scale and alginate dialdehyde (ADA)-Gel for the fabrication of 3D cell-laden hydrogels using mouse pre-osteoblast MC3T3-E1 cells was revealed as a suitable biomaterial ink formulation with great potential for 3D bioprinting for bone TE applications [62].…”
Section: Gelatinmentioning
confidence: 99%
“…With high surface area and unique structural shape, inorganic additives can significantly influence the properties of 3D scaffolds with tailored functionalities. In bone tissue engineering, inorganic materials-reinforced bioink formulations have been reported with successful outcomes in many studies using different materials and designs [4,[24][25][26][27][28]. Utilizing both organic and inorganic materials in a composite structure is a suitable approach to mimic the bone tissue extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…However, further in vitro cellular investigation using keratinocytes must be conducted to outline the potential for a tissue-engineered skin graft. Additionally, Özenler et al have demonstrated that the incorporation of fish scale into alginate dialdehyde-bioink can significantly enhance the mechanical properties of the 3D graft and evoke a favorable biological response to cells …”
Section: Introductionmentioning
confidence: 99%